2017
DOI: 10.2147/opth.s137712
|View full text |Cite
|
Sign up to set email alerts
|

Epithelium-on photorefractive intrastromal cross-linking (PiXL) for reduction of low myopia

Abstract: PurposeTo report the 9–12-month outcomes of a novel procedure for reduction of low myopia through epithelium-on photorefractive intrastromal cross-linking (PiXL) with customized control of topographic distribution of ultraviolet (UV)-fluence.MethodMyopic patients with normal (non-ectatic) corneas underwent the PiXL procedure for reduction of low myopia. PiXL treatments were delivered through selective application of UVA light based on the refractive error of each patient. Clinical evaluation included safety (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 15 publications
3
29
0
Order By: Relevance
“…Early clinical results support the ability of PiXL to predictably flatten a myopic cornea without significant changes to the endothelial cell count (ECC) or corneal clarity Nordstrom et al 2017). Lim et al (2017) followed eight subjects after PiXL in healthy myopic eyes, reporting a mean improvement of 0.25 LogMAR (2.5 Snellen lines) in uncorrected distance visual acuity at 1-year follow-up.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Early clinical results support the ability of PiXL to predictably flatten a myopic cornea without significant changes to the endothelial cell count (ECC) or corneal clarity Nordstrom et al 2017). Lim et al (2017) followed eight subjects after PiXL in healthy myopic eyes, reporting a mean improvement of 0.25 LogMAR (2.5 Snellen lines) in uncorrected distance visual acuity at 1-year follow-up.…”
Section: Introductionmentioning
confidence: 88%
“…Lim et al. () followed eight subjects after PiXL in healthy myopic eyes, reporting a mean improvement of 0.25 LogMAR (2.5 Snellen lines) in uncorrected distance visual acuity at 1‐year follow‐up.…”
Section: Introductionmentioning
confidence: 99%
“…Kanellopoulos first described the preliminary results for low myopic correction [ 98 ]. Lim et al reported on the results of PiXL for the treatment of low myopia in a cohort of 14 eyes with a 1 year followup [ 99 ]. High fluence UV-A irradiation ranging from 10-15 J/cm was delivered over a 4.5mm central zone.…”
Section: Customised Cross-linkingmentioning
confidence: 99%
“…demonstrated the results in a cohort of 14 eyes with a mean reduction in spherical equivalent of 0.72 ± 0.43D using the epithelium on approach. [ 2 ] Elling et al . demonstrated superior visual outcomes in 26 eyes undergoing PiXL following epithelial debridement.…”
Section: Discussionmentioning
confidence: 99%